Budaya Hukum Yang Hidup Dalam Masyarakat Indonesia Ditinjau Berdasarkan KUHP Nasional Nomor 1 Tahun 2023 - Andi Wulan Rahmadania; Muhammad Rizcky Afriyandi; Masayu Nilam Permata Sari; Elsi Kartika Sari (CV. ULIL ALBAB CORP, 2025)
Legal culture is a reflection of the mindset, attitudes, and behavior of society towards applicable legal regulations, playing an important role in the formation of legal awareness. In Indonesia, legal culture is formed from a combination of customary values, religion, and the influence of the colonial legal system. Amendments to the Criminal Code (KUHP) through Law Number 1 of 2023 replace the old Criminal Code left behind by the Dutch which is considered no longer relevant, by adjusting criminal regulations to the values ​​of modern society and paying attention to customary law as